Pemetaan Sumberdaya Subak Berbasis Remote Sensing dan Geographic Information System di Subak Juwuk dan Subak Lebo, Kecamatan Sukawati, Kabupaten Gianyar - ARGUMENTA TEO VELUS SITEPU; INDAYATI LANYA; I GUSTI PUTU RATNA ADI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Remote Sensing and Geographics Information System-Based Mapping of Subak Resources in Subak Juwuk and Subak Lebo, Sukawati Subdistrict, Gianyar Regency Based on Gianyar District Regulation No.16 of 2012 on Spatial Plan, Subak Juwuk and Subak Lebo rice fields in Sukawati Subdistrict, Gianyar Regency are designated as Green Open Space areas. Therefore, the mapping of remote sensing-based subak resources and Geographic Information System (GIS) is carried out to support the sustainability of sustainable food agricultural land. The objectives are: (1) identifying and describing potential subak resource (land resources, artificial resources, agricultural resources, and human resources), (2) inform the database of subak (land resources, artificial resources, agricultural resources, and human resources), (3) create a map of rice field ownership in Subak Juwuk and Subak Lebo, and (4) create farmer status maps and human resources based on remote sensing and geographic information systems. Research methods use: (1) literature study, (2) satellite image analysis, (3) tentative mapping of land ownership, (4) resource information arranging. The result of research: Rainfall 1300-1600 mm/year, slope 0-3%, land family Typic Fragiaquepts. Length of irrigation Subak Juwuk: 1300m; Subak Lebo: 1000m, types of secondary, tertiary irrigation. Types of rice, chili and tobacco commodities. Productivity 6 tons/ha. Subak Juwuk: owner 20 peoples area of 4,96 ha, sharecroppers 65 peoples area of 18 ha; Subak Lebo: owner 20 peoples area of 3,50 ha, sharecroppers 55 peoples area of 14,76 ha. The average age of farmers 40-80 years, average level of education of farmers in general are high school graduates. Mapping of agricultural land resources and geospatial-based human resources are very fast and accessible.